Temperature rise and Knoop hardness promoted by different light-curing units
This study characterized the light emitted by a quartz-tungsten-halogen (QTH) and three light-emitting diode (LED) light curing units (LCUs) and investigated the temperature rise and composite hardness promoted by these sources. XL2500 QTH (3M ESPE), Freelight LED (3M ESPE), Ultrablue Is LED (DMC) and Cool Blue Wand LED (Milestone Scientific) were investigated. The irradiance was measured with a power meter, and the light spectral distribution obtained with a spectrometer. Temperature rise was recorded using a thermocouple connected to a digital thermometer during light-activation of Filtek Z250 (3M ESPE) resin composite. Data were submitted to ANOVA and Tukey’s test (α=0.05). Knoop hardness was assessed at different composite depths (20, 1000 and 1980μm), and data submitted to split-plot design two-way ANOVA and Tukey’s test (α=0.05). Correlation between irradiance and temperature rise was investigated by Pearson’s test. All units presented 95% of irradiance between 400-515nm. Temperature rise means (ºC) varied between 1.05